Production Of Anti-Fungal Agent By Schizophyllum Commune Against Wood-Degrading Fungi Of Rubberwood - Teoh, Yi Peng @ Teng Yi Peng (2014)
Wood-degrading fungi are serious threat to rubberwood. Chemical preservatives commonly used in rubberwood preserving industry become awareness as it give impact to health and environmental problem. Biological control may be used as an alternative method to solve this problem. In this study, twelve locally isolated wild strains of wood-degrading fungi were screened for their capability to produce antifungal agent. Results showed that methanol extract of Schizophyllum commune biomass provided the highest antifungal activity among the tested fungi with minimum inhibitory concentration (MIC) ranging from 0.1 to 5.0 μg/μl. Chemical compound presence in the biomass extract was analyzed via gas chromatography-mass spectrometry (GC-MS) and high performance liquid chromatograph (HPLC). It was found that 4H-pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl- (DDMP), a flavonoid fraction, was presence in the biomass extract. Optimization strategy based on one-factor-at-a-time (OFTA) method and statistical tool were employed to optimize the growth of S. commune in shake flask culture. Based on Plackett-Burman design (PBD), the variables such as yeast extract, glucose and MgSO4·7H2O significantly affected the fungus growth. The optimal values of these process variables were determined using Response Surface Methodology (RSM) coupled with Box-Behnken design (BBD). For the extraction of antifungal agent, the optimum conditions were 70.75% (v/v) methanol, 29 °C, and 145 rpm. All optimization studies were verified and the experimental data fitted well to the selected models with error percentage less than 1%.